Integrated water resources management in Nepal: key stakeholders’ perceptions and lessons learned - Suhardiman, Diana; Clement, Floriane; Bharati, Luna (Informa UK Limited, 2015)
Integrated water resources management (IWRM) has been prescribed in the global water policy literature for decades. This article looks at how the concept has been applied in Nepal. It highlights the normative approach in IWRM policy formulation, the existing institutional barriers to apply it and how these resulted in the framing of IWRM ‘implementation’ as merely a compilation of donor-funded projects. Current discourse on IWRM highlights the need to shift the emphasis from national policy formulation to local adaptive, pragmatic approaches to IWRM. This article brings to light the need to identify potential entry points to scale up locally rooted water management approaches towards the development of nested institutional set-ups in water resources management.